Effect of Skin-contact Time and Temperature on Juice and Wine Composition and Wine Quality - Maraisa, J.; Rapp, A. (South African Journal of Enology and Viticulture, 2017)
The effect of skin-contact time (4 hours and 15 hours) and temperature (0°C and 20°C for 20 hours) on terpene, phenol and acetamide concentrations in Gewiirztraminer juices and wines and on wine quality was investigated. An increase in skin-contact time and temperature generally resulted in increases in terpene, phenol and N-(3-methylbutyl)-acetamide concentrations. Wines produced from juice subjected to low temperature skin-contact were generally of a higher quality than wines produced from free-run juice or juice subjected to skin-contact at elevated temperatures.